The Roles of Doxorubicin in Hepatocellular Carcinoma - Kin Tam (International Association of Physical Chemists (IAPC), 2013)
Liver cancer is the third most common cause of death from cancer worldwide. Hepatocellular carcinoma (HCC) accounts for 80 - 90 % of all primary liver cancers. The mortality of HCC is high, and the treatment options are limited. Doxorubicin exhibits a broad spectrum of antitumor activity. When administrated via the hepatic artery, doxorubicin showed antitumor effects and partial response in HCC patients. In this mini review, we will first outline the treatment options for HCC. Then, we will briefly discuss the pharmacological, toxicological and pharmacokinetic aspects of doxorubicin. Finally, we will review the new developments and future directions of using doxorubicin in the therapy of HCC.